GERAKAN NII KARTOSOEWIRJO (KW IX) - Asep Zaenal Ausop (Fakultas Seni Rupa dan Desain ITB, 2009)
NII (The Indonesian Islamic State) called DI (Dar al-Islam) is an Islamic movement organization (Harakah IslÃ¡miyyah) is led by Maridjan Sekarmadji Kartosoewirjo (MSK), a prominent of Masyumi from West Java. This organization has its own soldiers called TII or The Islamic Indonesian Soldiers. They proclaimed